Characterization of the response of fibre Bragg gratings fabricated in stress and geometrically induced high birefringence fibres to temperature and transverse load. - Chehura, Edmon; Ye, Chen-Chun; Staines, Stephen E.; James, Stephen W.; Tatam, Ralph P. (Institute of Physics (IOP), 2004)
The transverse load and temperature sensitivities of fibre Bragg gratings (FBGs) fabricated in a range of commercially available stress and geometrically induced high birefringent (HiBi) fibres have been experimentally investigated. The wavelength reflected by the FBG in each polarization eigenmode was measured independently and simultaneously using a custom designed interrogation system. The highest transverse load sensitivity, of 0.23 ± 0.02 nm/(N/mm), was obtained with HiBi FBGs fabricated in elliptically clad fibre. This was higher than for any other HiBi fibre, which, coupled with the small diameter of the fibre, makes it a good candidate for an embedded or surface mounted strain sensor. The highest temperature sensitivity of 16.5 ± 0.1 pm °C-1, approximately 27% greater than any other fibre type, was obtained with the HiBi FBG fabricated in Panda fibre. HiBi FBG sensors fabricated in D-clad fibre were the only ones to exhibit identical temperature sensitivities for the slow and fast axes (11.5 ± 0.1 pm °
Keywords: Transverse strain; birefringent fibres; multi-axial strain; 3D strain; temperature; fibre Bragg grating sensors